THE INFLUENCE OF MOBILE PHONES ON STUDENT DISCIPLINE IN ISLAMIC EDUCATION SUBJECT - Adinata, Muhammad Surya; Amaliyah, Laeli (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The rapid development and progress of science and communication in this era of globalization has had a major impact on society. This impact also brings convenience in various activities. In this case the impact is also experienced by students. Where the impact affects the activity or discipline of students. The purpose of this study was to determine the effect of mobile phones on students' discipline in PAI class VIII B at SMPN 2 Maesan. The type of this research is to use a simple regression quantitative research type with a total of 33 students including 15 boys and 18 girls. The results of this study are that the correlation / relationship (R) value is 0.167. From this output, the coefficient of determination (R Square) is 0.028 which implies that the influence of the independent variable (mobile phone) on the dependent variable (Student Discipline Attitude) is 0.28%. It can be concluded from the explanation above that the influence of the variable (X) Mobile on the variable (Y) Student discipline attitude has a correlation with a low degree of relationship, and the form of the relationship is negative according to the table above (coefficient interval and relationship level) between 0.20-0.399.